A Context-Dependent Role for MiR-124-3p on Cell Phenotype, Viability and Chemosensitivity in Neuroblastoma in vitro - Nolan, John C.; Salvucci, Manuela; Carberry, Steven; Barat, Ana; Segura, Miguel F.; Fenn, Justine; Prehn, Jochen H. M.; Stallings, Raymond L.; Piskareva, Olga (Frontiers in Cell and Developmental Biology, 2020)
Neuroblastoma (NB) is a neural crest-derived tumour, which develops before birth or in early childhood, with metastatic dissemination typically preceding diagnosis. Tumours are characterised by a highly heterogeneous combination of cellular phenotypes demonstrating varying degrees of differentiation along different lineage pathways, and possessing distinct super-enhancers and core regulatory circuits, thereby leading to highly varied malignant potential and divergent clinical outcomes. Cytoskeletal reorganisation is fundamental to cellular transformations, including the processes of cellular differentiation and epithelial to mesenchymal transition (EMT), previously reported by our lab and others to coincide with chemotherapy resistance and enhanced metastatic ability of tumour cells. This study set out to investigate the ability of the neuronal miR-124-3p to reverse the cellular transformation associated with drug resistance development and assess the anti-oncogenic role of this miRNA in in vitro models of drug-resistant adrenergic (ADRN) and mesenchymal (MES) neuroblastoma cell lines. Low expression of miR-124-3p in a cohort of neuroblastomas was significantly associated with poor overall and progression-free patient survival. Over-expression of miR-124-3p in vitro inhibited cell viability through the promotion of cell cycle arrest and induction of apoptosis in addition to sensitising drug-resistant cells to chemotherapeutics in a panel of morphologically distinct neuroblastoma cell lines. Finally, we describe miR-124-3p direct targeting and repression of key up-regulated cytoskeletal genes including MYH9, ACTN4 and PLEC and the reversal of the resistance-associated EMT and enhanced invasive capacity previously reported in our in vitro model (SK-N-ASCis24).